The relationship between childhood behaviour disorders and unintentional injury events - Bruce, Beth (Pulsus Group Inc, 2007)
OBJECTIVE: To examine the controversy regarding the existence of a relationship between behavioural disorders and unintentional injuries in children. DESIGN: A retrospective cohort analysis of children between six and 19 years of age, who were diagnosed with attention deficit hyperactivity disorder (ADHD) only (n=955), ADHD plus conduct problems (CP) (n=160), or CP only (n=234), were compared with a nondisorder group of children (n=21,308) for unintentional injury events resulting in a physician office or emergency room visit, or hospitalization. RESULTS: The risk of an injury event was greater among children with a behaviour disorder diagnosis and severity of injury varied among the behaviour disorder groups. Children with ADHD were the only disorder group at increased risk for all three injury outcomes. Children with a comorbid diagnosis were at a greater risk for both minor and more serious emergency injury visits, and children with CP only were at greatest risk for the most serious injuries (hospital admission). CONCLUSIONS: These findings provide further support that children with ADHD are at an increased risk for not only hospitalized injury events but also minor injury events. In addition, these findings provide evidence that serious injuries are more likely to be experienced by children with CP.